ТЕОРЕТИЧНІ ОСНОВИ ФІЗИЧНОГО ВИХОВАННІ! У ФОРМУВАННІ КУЛЬТУРИ ЗДОРОВОГО СПОСОБУ ЖИТТЯ СТУДЕНТІВ (Педагогіка вищої та середньої школи, 2010)
Theoretical bases of forming of culture of healthy way of life of physical education facilities are examined in the article, which functions in a cultural environment and carries cultural values for the use in everyday life of students.